2019
DOI: 10.1097/iop.0000000000001189
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Features and Clinical Course in Patients With Recurrent or Malignant Orbital Solitary Fibrous Tumor/Hemangiopericytoma

Abstract: Purpose: A risk assessment score for metastasis based on age, tumor size, and mitotic figures has been suggested for nonorbital solitary fibrous tumor (SFT)/hemangiopericytoma. The authors herein examine the clinicopathological features of recurrent and metastatic orbital SFT and evaluate the existing risk assessment score for orbital SFT. Methods: The American Society of Ophthalmic Plastic and Reconstructive Surgery Oncology Database was queried for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…In the present research, clinical, imaging, and pathological features of 3 patients with recurrent orbital SFT were retrospectively compared. We also used the PubMed database to search for recurrent orbital SFT, and 21 related literatures were selected to explore their clinical and pathological features [3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present research, clinical, imaging, and pathological features of 3 patients with recurrent orbital SFT were retrospectively compared. We also used the PubMed database to search for recurrent orbital SFT, and 21 related literatures were selected to explore their clinical and pathological features [3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The MRI ndings of orbital SFT showed that lesions had equal density with the gray matter on T1WI, and values of signal intensity on T2WIs were controversial [30][31][32][33]. Previous studies reported that orbital SFT is rich in brous matrix and T2WI should be dominated by a low signal intensity, however, in several reported cases of malignant orbital SFT, cystic degeneration could be detected with a high signal intensity, suggesting that cystic degeneration could be related to malignant transformation [4,34]. In addition, the contrast-enhanced MRI showed enhanced SFT, while the enhancement can be uniform or uneven, and it may be associated with the distribution of blood vessels and capillary permeability [35][36][37].…”
Section: Imaging Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our case, 2 patients were found to have relapsed, with the lesions growing more rapidly and more invasive after recurrence. In the cohort of recurrent orbital hemangiopericytoma/SFT, median time to recurrence was 4 years underscoring the importance of careful continued follow-up [18] . This group were followed up from 7 months to 8 years, and the median was 2 years 10 months.…”
Section: Treatment and Prognosis Of Orbital Sftmentioning
confidence: 99%